Hand Hygiene Practices during the COVID-19 Pandemic in Northern Italy: Assessment of Compliance Rates Measured by Direct Observation and Alcohol-Based Handrub Usage - Costanza Vicentini; Giulia Libero; Valerio Bordino; Carla Maria Zotti (MDPI AG, 2022)
Hand hygiene (HH) is among the most effective measures for reducing the transmission of healthcare-associated infections and SARS-CoV-2. We aimed to assess HH practices among healthcare workers (HCWs) of three hub hospitals in Northern Italy during the COVID-19 pandemic, by assessing HH compliance measured by direct observation and alcohol-based handrub usage. An observational study was conducted over a period of three months, between February and April 2021. HH compliance audits were conducted using the WHO My 5 Moments for HH approach. Multivariable logistic regression was used to evaluate independent predictors of HH compliance: ward type, HCW category and HH indication. Spearman correlation was used to investigate the relationship between HH compliance and alcohol-based handrub consumption. In total, 2880 HH opportunities were observed, with an overall compliance of 68%. Significant differences were found in compliance rates across ward types, HCW categories and HH indications. The mean alcohol-based handrub usage among included wards was 41.63 mL/PD. No correlation was identified between compliance rates and alcohol-based handrub consumption (ρ 0.023, p 0.943). This study provided a snapshot of HH practices in a pandemic context, which could be useful as a reference for future studies.